Graphical User Interfaces for R - Valero Mora, Pedro Miguel (2012)
Since R was first launched, it has managed to gain the support of an ever-increasing percentage of academic and professional statisticians. However, the spread of its use among novice and occasional users of statistics have not progressed at the same pace, which can be atributed partially to the lack of a graphical user interface (GUI). Nevertheless, this situation has changed in the last years and there is currently several projects that have added GUIs to R. This article discusses briefly the history of GUIs for data analysis and then introduces the papers submitted to an special issue of the Journal of Statistical Software on GUIs for R.